The impact of the COVID-19 pandemic on the epidemiology of whooping cough (review of literature) - N. A. Filaeva; I. V. Babachenko; N. N. Kurova (Журнал инфектологии, 2025)
The review presents current information on the epidemiological situation with whooping cough during the COVID-19 pandemic and in the post-pandemic period: the dynamics and age structure of the incidence in different countries of the world are shown with an analysis of the causes of changes. According to the literature, the effect of isolation measures on the incidence of whooping cough in 2023–2024 is described using the example of Japan, as well as vaccination of pregnant women against whooping cough using the example of South Korea. Some aspects of the pathogenesis of whooping cough and COVID-19 are presented, which can affect the course of combined diseases in children. The article presents an analysis of two described clinical cases in unvaccinated children aged 1 and 4 months, showing the dominance of typical clinical manifestations of whooping cough, the absence of fever and intoxication characteristic of COVID-19, the development of bronchiolitis with respiratory failure, which aggravated the severity of the disease. This justifies the advisability of examining patients with whooping cough with atypical respiratory manifestations for a new coronavirus infection, and for whooping cough – COVID-19 convalescents with a long cough.